ISOLASI, KARAKTERISASI, DAN IDENTIFIKASI BAKTERI PADA LELE DUMBO YANG TERSERANG PENYAKIT DI KABUPATEN BANYUMAS - Dini Siswani Mulia; Heri Maryanto; Cahyono Purbomartono (Sainteks, 2011)
The aim of this research is to isolate, characterize, and identify bacteria on infected African catfish in Banyumas Regency. The researcher used survey method and purposive random sampling technique. Samples were infected African catfish. They were taken from three areas that had potential cultivation for African catfish in Banyumas, namely Rempoah, Kebanggan, and Singosari. In each area, the researcher chose two African catfish cultivating ponds randomly and each pond was taken randomly 3 fishes. Symptoms of the disease in African catfish sample were carefully observed, both externally and internally with surgically. External observation covered wounds and bleeding in some parts of the body, sores or ulcers on the body, protruding eyes, while the internal observation included kidney. Isolation of bacteria carried from the skin (scales), body sores, fin, and kidney. Characterization was done by observing the structure of macroscopic, microscopic, and biochemical tests. The results indicated that 130 isolates of bacteria, and identified to be genus Alcaligenes, Bacillus, Arachnia, Acidomonas, Aeromonas, Amphibacillus, Salmonella, Neisseria, Pseudomonas, Micrococcus, and Clostridium. Keywords: isolation, characterize, identify, bacterium, African catfish, Banyumas regency